AN INVESTIGATION OF THE EFFECT OF FAMILY BACKGROUND VARIABLES ON INNOVATION PERCEPTIONS OF ENGINEER AND TEACHER CANDIDATES - ÇORLU, Mehmet Ali; AYDIN, Emin (The Eurasia Proceedings of Educational and Social Sciences, 2016)
The aim of this study is to investigate the innovation perceptions of teacher candidates in the areas of mathematics, science and social sciences. The data collection tools are the Turkish versions of the Individual Innovativeness Scale (IIS) and Big5 Scale for personality characteristics. Multivariate linear regression is the main data analysis technique. Results indicate that 47% of the variation in the IIS is explained by the independent variables.